Strategi Branding, Marketing dan Reputasi dalam Meningkatkan Daya Saing Sekolah - Puji Astuti; Teguh Trianung; Heru Santosa (Universitas Negeri Malang, 2020)
Abstract: In the digital era, significant transformations have taken place within the education sector, particularly in how institutions manage and organize their operations. With the rapid advancement of technology and the increasing reliance on digital tools, educational institutions are presented with new opportunities to boost their competitiveness. One of the key ways they can achieve this is through the strategic use of branding, marketing, and reputation management. These elements play a crucial role in shaping a school’s public image and enhancing its attractiveness to potential students and stakeholders. This article delves into the synergistic roles of branding, marketing, and reputation management strategies in strengthening a school’s competitive position. The research employs a qualitative approach, utilizing a case study method to explore how these strategies are implemented in real-world educational settings. Data collection methods include in-depth interviews with key stakeholders, participant observations, and documentary analysis, ensuring a comprehensive understanding of the subject. The findings of this research indicate that the integration of branding, marketing, and reputation management strategies can significantly elevate a school’s ability to stand out in a competitive market. Institutions that successfully highlight their unique identity, effectively utilize technology for promotional activities, and maintain a positive reputation are better positioned to attract prospective students and parents. Additionally, the study suggests that these strategies must work in harmony to achieve the desired outcomes, as each element complements the others. Ultimately, schools that adopt a holistic approach to these strategies are more likely to succeed in an increasingly competitive educational environment, where reputation and visibility play pivotal roles in attracting students and fostering institutional growth. Keywords: Branding, Marketing, Reputasi Sekolah Abstrak: Era digital telah membawa perubahan signifikan dalam sektor pendidikan, terutama dalam cara institusi mengelola dan menyelenggarakan operasional mereka. Dengan pesatnya perkembangan teknologi dan ketergantungan yang semakin besar pada alat digital, institusi pendidikan memiliki peluang baru untuk meningkatkan daya saingnya. Salah satu cara utama untuk mencapai hal ini adalah melalui penggunaan strategi merek, pemasaran, dan manajemen reputasi yang efektif. Elemen-elemen ini memiliki peran penting dalam membentuk citra publik sekolah dan meningkatkan daya tariknya bagi calon siswa dan pemangku kepentingan. Artikel ini membahas peran sinergis dari strategi merek, pemasaran, dan manajemen reputasi dalam memperkuat posisi kompetitif sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus untuk mengeksplorasi bagaimana strategi-strategi ini diterapkan dalam pengaturan pendidikan dunia nyata. Teknik pengumpulan data yang digunakan meliputi wawancara mendalam dengan pemangku kepentingan utama, observasi partisipan, dan analisis dokumentasi, guna memperoleh pemahaman yang komprehensif mengenai topik ini. Hasil penelitian ini menunjukkan bahwa integrasi strategi merek, pemasaran, dan manajemen reputasi dapat secara signifikan meningkatkan kemampuan sekolah untuk menonjol di pasar yang kompetitif. Institusi yang berhasil menonjolkan identitas unik mereka, memanfaatkan teknologi untuk kegiatan promosi, dan menjaga reputasi yang baik di mata publik lebih berpotensi untuk menarik calon siswa dan orang tua. Selain itu, penelitian ini menyarankan bahwa strategi-strategi ini harus bekerja secara harmonis untuk mencapai hasil yang diinginkan, karena masing-masing elemen saling melengkapi. Pada akhirnya, sekolah-sekolah yang mengadopsi pendekatan holistik terhadap strategi-strategi ini lebih mungkin untuk berhasil di lingkungan pendidikan yang semakin kompetitif, di mana reputasi dan visibilitas memainkan peran penting dalam menarik siswa dan mendukung pertumbuhan institusi. Kata kunci: Branding, Marketing, Reputasi Sekolah